Global campaigning initiatives for socio-economic development - Carvalho, Luøsa Cagica, 1970-; Madeira, Maria José, 1963- (Information Science Reference, 2019)
"This book focuses on the role and contribution of global campaigns, in accelerating economic growth with a multiplier effect on the national income by inviting global participation in all the sectors of socio economic development"--